Hemobilia following Percutaneous Liver Biopsy in the Setting of Malignancy (with Video): Diagnosis and Management of a Rare Cause of Upper Gastrointestinal Bleeding - B. Pabla; M. Porayko (Case Reports in Gastrointestinal Medicine)
A 57-year-old gentleman with a past medical history of well-differentiated pancreatic neuroendocrine tumor (NET) with liver metastases was transferred to our hospital with abdominal pain. He underwent percutaneous liver biopsy three days prior to admission as a part of a study protocol for treatment of his progressive NET. He developed gastrointestinal bleeding and was found to have a distended gallbladder filled with high density material on ultrasound. During initial upper endoscopy, it was noted that he had blood emanating from the duodenal papilla consistent with hemobilia and he was ultimately diagnosed with post-liver biopsy hemorrhage. At first, he was managed conservatively with supportive care, but bleeding persisted resulting in the need for arterial embolization as a more effective treatment modality. Hemobilia is a rare entity and in the modern era it is most commonly the result of iatrogenic injury. Appropriate management depends on the underlying etiology with most cases resolving with conservative management. The avoidance of unnecessary surgery and the use of embolization are key principles in management.